The PENGARUH PENGEMBANGAN KARIR, LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN YANG DIMODERASI OLEH MOTIVASI KERJA DI CV HARAPAN BARU SULUT - Fiki Jaya Bawamenewi; Silvya L. Mandey; Lucky O. H. Dotulong (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
The purpose of this study is to determine the direct influence of career development, work environment and workload on employee work motivation and work spirit. The influence of career development, work environment and workload on employee work spirit through work motivation at CV Harapan Baru Sulut. This study is a quantitative study with an associative approach. The sample used a saturated sample with a total of 47 respondents. The results of the study indicate that: career development has a significant effect on work motivation, the work environment does not have a significant effect on work motivation, workload has a significant effect on motivation, career development does not have a significant effect on work spirit, the work environment does not have a significant effect on work spirit, workload has a significant effect on work spirit, work motivation does not have a significant effect on work spirit, career development through work motivation does not have a significant effect on work spirit, the work environment through work motivation does not have a significant effect on work spirit and workload through work motivation does not have a significant effect on work spirit at CV. Harapan Baru Sulut.